2005
DOI: 10.1002/cbdv.200590029
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Activities of Chalcone and 1,5-Benzothiazepine Derivatives: Promising New Free-Radical Scavengers, and Esterase, Urease, and?-Glucosidase Inhibitors

Abstract: A series of 2,4-diaryl-2,3,4,5-tetrahydro- (36-40) and 2,4-diaryl-2,3-dihydro-1,5-benzothiazepines (25-35) have been synthesized from the corresponding chalcones 1-24. Both the benzothiazepines and chalcones were evaluated as DPPH free-radical scavengers and as inhibitors of cholinesterases, urease, and alpha-glucosidase. Compounds 2, 5, 6, 7, 10, 13, 18, 21, 36a, 37a, 37b, and 39a showed significant cholinesterase inhibiting activities. Among the 15 dihydro-1,5-benzothiazepines, 26, 32, and 35 exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…The synthesis of variety of chalcones 2, 3-dihydro-1, 5-benzothiazepines and their corresponding 2,3,4,5-tetrahydrobenzothiazepines has earlier been reported [16] and studies on their AChE and BChE inhibitory potential were also carried out. However, it was found that only 2,3,4,5-tetrahydrobenzothiazepines showed a significant AChE inhibition; Therefore, it was considered worthwhile to have a deeper insight in the mechanism of interaction of these benzothiazepines with AChE by kinetics and molecular docking studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of variety of chalcones 2, 3-dihydro-1, 5-benzothiazepines and their corresponding 2,3,4,5-tetrahydrobenzothiazepines has earlier been reported [16] and studies on their AChE and BChE inhibitory potential were also carried out. However, it was found that only 2,3,4,5-tetrahydrobenzothiazepines showed a significant AChE inhibition; Therefore, it was considered worthwhile to have a deeper insight in the mechanism of interaction of these benzothiazepines with AChE by kinetics and molecular docking studies.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition kinetics, pharmacological profiles, molecular docking, 3D-QSAR (CoMFA and CoMSIA) studies have also been conducted for a good number of compounds [11][12][13][14][15]. Continuing our on going search for new inhibitors of therapeutically significant enzymes through highthroughput screening assays, we recently synthesized benzothiazepines 1-3, with valuable AChE inhibitory potential [16].…”
Section: Introductionmentioning
confidence: 99%
“…3-bromo and 3-chloro-have been found to possess high values of hydrophobicity constant (π), octanol-water partition coefficient (log P) and molar volume (Vm) with the exception of methoxy substituted chalcones. Moreover, the manifested bactericidal effect was also found to be facilitated by the presence of electron acceptors on the phenyl ring of chalcones of Set 1, the only exception being the nitro group which irrespective of its position on the phenyl ring suppressed the activity of all three regioisomeric chalcones (18)(19)(20). It may therefore be implied that the lipophilicity of the compounds appeared to be the main predictor of bactericidal activity.…”
Section: Synthesismentioning
confidence: 94%
“…We have reported earlier the design and synthesis of a 120-member library and its screening against a number of bacterial strains and the lead structure was identified through deconvolution based on positional scanning protocol. 18 Prompted by the findings and in continuation to our interest in the synthesis of biodynamic chalcones, 19,20 we synthesized a parallel library of 3-hydroxy-aryl and heteroaryl chalcones in order to study their bactericidal potential against B. bronchiseptica. Although we tested these compounds also against a number of other gram-positive and gram-negative bacterial strain namely, Micrococcus leuteus ATCC10240, Pseudomonas picketti ATCC 49129, Escherichia coli ATCC 15224, Enterobacter aerogenes ATCC 13048, and Salmonella setubal ATCC 19196, however, with the exception of B. bronchiseptica all the compounds were found to be generally inactive against these strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation